Regla de Reconocimiento y contenidos mínimos de derecho natural en Hart: en pos de una articulación (2021)
In this article I propose a connection between Hart’s rule of reconigtion and the thesis of minimum contents of natural law of the same author. The recognition rule is understood as a conventional rule constituted by the practice of judicial officials in charge of applying validity criteria to determine whether particular norms belong to the system. The minimum contents of natural law constitute the basis of human tendencies or instincts. in his quest for survival. From the approaches of Marmor and Raz, it is proposed that in the recognition rule the minimum contents of natural law constitute the first filter for evaluating the validity of the particular legal norms subject to legal recognition, which provides solidity and significant consistency to the thesis of discretion and separability of the Hartian theory.